(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This study focuses on the role and management of extra-budgetary funds in budgetary organizations, the features of their formation, use and control. Normative acts and practices related to extra-budgetary funds in the social sphere are studied, as well as models of state participation in the financing of social protection are analyzed. The paper proposes methods for optimizing the accounting and control of extra-budgetary funds to increase the efficiency and effective use of budgetary funds. Resources.